Soccer Training Methodology: A Coach's Vision - Alberto Sanmiguel-Rodríguez; Vicente Romo-Pérez; Victor Arufe-Giráldez; Oliver Ramos-Álvarez (OVS LLC, 2023)
Background. Based on the fundamental principles of training, the methodology that each coach develops in the planning of sessions can be effective in improving the performance of their athletes. Study purpose. Therefore, the general objective pursued in this study was to find out the type of work carried out by the coaching staffs in their different teams/clubs. Materials and methods. For this work, a descriptive cross-sectional study was carried out on a sample of 517 coaches from different divisions and nationalities. To characterise the sample, descriptive measures were used and Pearson's chi-square was used to study whether there is a relationship between the variables studied. All statistical analyses were performed with Stata and statistical significance was always set at a p-value < 0.05. Results. The results indicated that the methodology preferred by the coaches for working on the technique was the Coerver and analytical methods. The global and analytical methods were the most used on average by the coaches for tactical work. The coaches, regardless of the division or category in which they train, indicated that strength is the most important capacity to work on. Conclusions. The results of this study can be very useful for future coaching staffs when distributing training sessions and workloads.